A STUDY OF THE PREVALENCE OF LEISHMANIASIS IN KIRKUK GOVERNORATE AND EVALUATION OF SOME IMMUNOLOGICAL AND BIOCHEMICAL INDICATORS IN LEISHMANIASIS PATIENTS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The current study was conducted on cases of Cutaneous Leishmaniasis Cutaneous infected with cutaneous Leishmaniasis that were received in hospitals in Kirkuk Governorate for the period from 1/7/2022 to 1/7/2023 retrospectively. 800 smears of skin lesions were examined under a compound microscope after being stained with Leishmaniasis stain or part of it was transplanted into the medium. Al Zarai (NNN) (Novy-MacNeal-Nicolle) at 23 C°. The results of the study showed that all samples were infected with a higher risk of infection by 40.92%, of which 25.6% were females and 15.75% were males. 45% infection rate. Also The study included the evaluation of immunological and some biochemical indicators in patients with Leishmaniasis Cutaneous. The current study included the collection of 100 blood samples from patients with Leishmaniasis Cutaneous whose ages ranged between (1-60) years for the period from 1/2/2023 to 1/5/2023. From the Oncology Hospital of the Medical City in Kirkuk Governorate the samples were divided into two groups: The first group (G1) which involve 60 samples from Leishmaniasis Cutaneous and 30 samples of healthy people. -The study included estimation of the levels of (Interferon-γ، Tumor necrosis factor ، IL-10، Iron)and liver function which include (AST،ALT) for the samples under study.The results obtained from the current study: - The INF-γ, TNF-α, IL-10 level significantly elevated (P≤0.05) in the serum of G1 compared to healthy group. -The liver function activity enzyme significantly elevated (P≤0.05) in the serum of G1 compared to the healthy. -The Iron level significantly decrease (P≤0.05) in the serum of G1 compared to the healthy group.